Strong Early Phase Parasympathetic Inhibition Followed by Sympathetic Withdrawal During Propofol Induction: Temporal Response Assessed by Wavelet-Based Spectral Analysis and Photoplethysmography - Wang, Hsin-Yi; Lo, Men-Tzung; Chen, Kun-Hui; Mandell, Susan; Chang, Wen-Kuei; Lin, Chen; Ting, Chien-Kun (Frontiers in Physiology, 2021)
Background: Induction of anesthesia with propofol is associated with a disturbance in hemodynamics, in part due to its effects on parasympathetic and sympathetic tone. The impact of propofol on autonomic function is unclear. In this study, we investigated in detail the changes in the cardiac autonomic nervous system and peripheral sympathetic outflow that occur during the induction of anesthesia. Methods: Electrocardiography and pulse photoplethysmography (PPG) signals were recorded and analyzed from 30 seconds before to 120 seconds after propofol induction. The spectrogram was derived by continuous wavelet transform with the power of instantaneous high-frequency (HFi) and low-frequency (LFi) bands extracted at 1-second intervals. The wavelet-based parameters were then divided into the following segments: (1) baseline (30 seconds before administration of propofol), (2) early phase (first minute after administration of propofol), and (3) late phase (second minute after administration of propofol) and compared with the same time intervals of the Fourier-based spectrum (high-frequency [HF] and low-frequency [LF] bands). Time-dependent effects were explored using fractional polynomials and repeated-measures analysis of variance. Results: Administration of propofol resulted in reductions in HFi and LFi and increases in the LFi/HFi ratio and PPG amplitude, which had a significant non-linear relationship. Significant between-group differences were found in the HFi, LFi, and LFi/HFi ratio and Fourier-based HF andLF after dividing the segments into baseline and early/late phases. On post-hoc analysis, changes in HFi, LFi, and the LFi/HFi ratio were significant starting from the early phase. The corresponding effect size (partial eta squared) was >0.3, achieving power over 90%; however, significant decreases in HF and LF were observed only in the late phase. The PPG amplitude was increased significantly in both the early and late phases. Conclusions: Propofol induction results in significant immediate changes in autonomic nervous system activity that include temporally relative elevation of cardiac sympathovagal balance and reduced sympathetic activity.